The Bonus That Wasn’t Out at Millennium Company - Yahya, Rohaziah; Sarif, Suhaimi; Zainudin, Dolhadi; Ismail, Yusof; Firmansah, Yayan (IIUM Journal of Case Studies in Management, 2025)
This case presents a challenge for Zulkarnain Bakar, an industrial relations analyst at Nusantara Equity Consultants (NEC), tasked with advising Millennium Company—a renowned food manufacturing firm—after its controversial decision to withhold staff bonuses in the pandemic year. Known for a harmonious partnership with the Union of Factory Workers (UFW) and a tradition of shared rewards, Millennium now faces mounting pressure from its union and internal stakeholders to balance contractual integrity with survival. The case requires Zulkarnain to examine the interplay between organizational values, collective bargaining agreements, legal frameworks, and ethical leadership. Should Millennium prioritize immediate contractual fulfillment, or adopt a stance of sustainable stewardship for long-term employment and stakeholder trust? The analyst must integrate legal, ethical, and socio-economic considerations to propose a path forward for all parties.